Multiple causations of hospitalizations due to mycoses in a Brazilian region: from anthropogenic to climate factors (Research, Society and Development, 2023)
Fungal infections are a public health problem. Mycoses are neglected, some are related to regions with low human development and under the influence of climatic conditions. The study aimed to analyze a series of hospitalizations due to mycoses (HM) that occurred in Minas Gerais, Brazil, from 1998 to 2018, as outcomes of anthropic and climate variability. We performed predictive analyses using Spearman’s rank correlation and logistic regression modeling to determine the correlation between HM and social, demographic, economic, epidemiological, and climate factors in Minas Gerais, Brazil. Data were obtained from national databases from 1998 to 2018. We found significant correlations between HM and population size, demographic density, health facilities (negative correlations), rural population, and coffee area harvested or cultivated (positive correlations), indicating that living in small urban centers is a strong predictor. We find weak but statistically significant associations between HM and meteorological conditions. Interestingly, the outbreak of hospitalizations matched La Niña events in the municipality with the highest frequency of hospitalization due to mycoses in Minas Gerais. Complex interactions among social, demographic, economic, and climatic factors drive mycoses dynamics. This work provides evidence that climatic and human activities influences hospitalizations due to mycoses in a Brazilian region.